Componential Analysis Of Meaning: Theoryand Applications - Widyastuti, Susana (English Education Department, Universitas Islam Indonesia, 2010)
There are many different ways to approach the problems of meaning, since meaning is related to many different functions of language. The meanings of words in a language are interrelated and they are defined in part by their relations with other words in the language. Analyzed in the same semantic domain, words can be classified according to shared and differentiating features. Breaking down the sense of a word into its minimal distinctive features, componential analysis of meaning can be a useful approach in the study of meaning, particularly in determining the meaning of a lexeme. Although componential analysis has some difficulties and limitations in its application, it is still used in modern linguistics.